Factors Related to Health Behaviors in Persons with Hypertension, Myanmar - Oo, Honey; Sakunhongsophon, Somnuk; Terathongkum, Sangthong (Makara Journal of Health Research, 2018)
Background: The aim of this study was to describe the relationships between personal and environmental factors and health behaviors in persons with hypertension. Methods: This was a cross-sectional study carried out using a convenient sample of individuals with hypertension from three community health centers in Yangon, Myanmar. Data were collected using a standardized interviewer- administered questionnaire consisting of six sections: demographic characteristics, Self-efficacy to manage Hypertension Scale, Health Behavior Questionnaire, Barriers to Health Promoting Activities Scale, Hypertension Knowledge Questionnaire, and Social Support Questionnaire. The data were analyzed using descriptive statistics, Chi-square, and Pearson's correlation coefficient. Results: Participants had a high level of perceived self-efficacy (42.13 ± 7.58), a low level of perceived barriers (35.32 ± 19.63), a poor social support (49.64 ± 8.51), a good level of hypertension knowledge (10.63 ± 1.90) and a moderate level of health behaviors (70.59 ± 12.39). Health behaviors had significant relationship with income, social support, hypertension knowledge and perceived barriers (r = -0.28, p = 0.004; r = 0.23, p = 0.019; r = 0.27, p = 0.006; r = -0.21, p = 0.034), respectively. Conclusions: These findings suggest that health behaviors in persons with hypertension can be improved using hypertension knowledge, social support, and decrease in perceived barriers.